1979
DOI: 10.1115/1.3448945
|View full text |Cite
|
Sign up to set email alerts
|

A Fundamental Criterion for the Application of Rotor Casing Treatment

Abstract: An experimental investigation has been carried out on the influence of grooved casing treatment on the stall margin of a compressor rotor. Tests were conducted with two rotor builds having different solidities (but all other parameters identical) so that one of the rotors exhibited a wall, or casing, type of stall, while the other showed a blade stall. It was found that the casing treatment, when compared to the solid casing, was very effective in increasing the stall margin of the wall stall configuration, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(61 citation statements)
references
References 0 publications
5
55
0
Order By: Relevance
“…Moore et al (1971) examined some casing treatment configurations and found that the circumferential groove could improve the stall margin and the peak efficiency of an axial-flow compressor rotor. Greitzer et al (1979) supposed the hypothesis that the casing treatment is effective only in a situation in which a wall stall exists. Crook et al (1993) numerically explored the effect of the grooved casing in suppressing the stall and identified two principal effects: suction of the high blockage fluid at the rear of the passage and energizing of the tip leakage flow.…”
Section: Introductionmentioning
confidence: 99%
“…Moore et al (1971) examined some casing treatment configurations and found that the circumferential groove could improve the stall margin and the peak efficiency of an axial-flow compressor rotor. Greitzer et al (1979) supposed the hypothesis that the casing treatment is effective only in a situation in which a wall stall exists. Crook et al (1993) numerically explored the effect of the grooved casing in suppressing the stall and identified two principal effects: suction of the high blockage fluid at the rear of the passage and energizing of the tip leakage flow.…”
Section: Introductionmentioning
confidence: 99%
“…This construction is characterized by great simplicity. Greitzer, E.M. et al have presented (5) the main conclusions of casing treatment (in the form of grooves and slots) use. Among these are the next: -The use of a grooved casing can provide substantial improvement in compressor stall range over a smooth wall casing (baseline).…”
Section: Casing Treatment Applicationmentioning
confidence: 99%
“…This procedure has been used in the past in other investigations (see Ref. 25 for a notable example), however the additional pressure drop associated with the radial profile generator, which will be a screen or combination of screens, is high enough so that we will use the auxiliary fan, which was brought under AFOSR funding, in combination with the compressor. The radial profiles of D-factor and static pressure rise divided by inlet dynamic pressure, AP/Q for this case are shown in Fig.…”
Section: Testing Of the Htf Stage Is Expected To Continue Through Latmentioning
confidence: 99%